Site characterisation and the effects of harvesting on soil tillage on the productivity of Eucalyptus grandis plantations in Brazil - Dedecek, R.A.; Bellote, A.F.J.; Gava, J.L.; Menegol, O. (Center for International Forestry Research, 2001)
Two commercial eucalypt sites were selected in Sao Paulo State, Brazil, to evaluate productivity and soil chemical and physical properties before clearcutting, and the effect of harvesting and soil tillage system on productivity of second rotation. At site 1, the Eucalyptus grandis plantation was 7 years old, on its first rotation, and reached 21 m mean height, 13.6 cm diameter breast height (dbh), an estimated commercial volume of 479 m3 ha-1 and a mean annual increment of 68 m3 ha-1 year-1. At site 2, E. grandis, also on its first rotation, but 12-years-old, had 25 m mean height, dbh 16 cm, an estimated volume of 662 m3 ha-1 and a mean annual increment of 55 m3 ha-1 year-1. Litter collected at site 2 before harvesting totalled 19.8 t ha-1, and after harvesting and new planting, litter left on surface totalled 2.64 t ha-1. At site 1, 31.3 t ha-1 of litter accumulated before harvesting and 7.6 t ha-1 after new planting. Soils of both sites are classified as Dark Red Latosol (Oxisol), having loam texture at site 2 and clay texture at site 1. Clay content difference between sites was around 10 %, available soil water content between sites varied less than 0.02 cm3 cm-3. Penetrometer soil resistance measured before harvesting and after new planting was less than 21 kg cm-2, at 50 cm besides tree row, on both sites. Greater soil resistance measured at tree row was found at 15-cm depth, in both sites. Soil of site 1 has greater CEC, base saturation and organic matter content compared to site 2. One year after planting eucalypts growing on soil tilled with subsoiler with one shrank were smaller at site 2.